Doomscrolling, Social Media, and Adolescent Depression: A Psychological and Neurological Perspective - Eun, Brian (Technium Social Sciences Journal, 2025)
This study ultimately aims to delineate the potential link between TikTok doomscrolling and behavioral problems amongst adolescent users while taking a psychological approach to analyze the insidious impacts of doomscrolling habits on individuals’ neurotic hormone levels. This study examines changes in stress-related hormones such as serotonin and dopamine in relation to doomscrolling behaviors. Furthermore, by bolstering the connection between neurotransmitter changes and behavioral changes analyzed from various research papers, this study aims to reveal a clear anatomical and psychological explanation behind rising behavior problems in young TikTok users. Hence, the study will establish specific guidelines warning young users of potential risks and promote safe social media usage.